Effects of non-indigenous plants on food sources of intertidal macrobenthos in Yueqing Bay, China: Combining stable isotope and fatty acid analyses. (31st August 2020) - Liao, Yibo; Shou, Lu; Tang, Yanbin; Zeng, Jiangning; Chen, Quanzhen; Yan, Xiaojun
Abstract: Plant invasions in coastal ecosystems may substantially alter benthic community composition and food web structure. We combined analyses of stable isotopes and fatty acids (FA) to examine the effects of two non-indigenous plants ( Spartina alterniflora and Kandelia candel ) on the food sources of three deposit feeders ( Assiminea brevicula, Cerithidea cingulata and Uca arcuata ) and a carnivorous opportunistic predator ( Periophthalmus modestus ) in Yueqing Bay, China. A wide range of differences was found in δ 13 C and δ 15 N among the macrobenthos. The deposit feeders in K . candel mangrove forest (KC) were markedly more 13 C-depleted than those in S . alterniflora marsh (SA) and unvegetated tidal flat (TF), unlike the carnivorous feeder. PERMANOVA showed that FA composition significantly differed among the macrobenthos. Diatom FA markers were higher in tissues of the deposit feeders than in the carnivorous feeder, and slightly lower in macrobenthos from the KC and SA habitats as compared with the TF. In contrast, vascular plant FA markers of macrobenthos were higher in the KC and SA than in the TF, indicating the contribution of mangrove and Spartina detritus to the consumers. The findings show that the food sources of macrobenthos were markedly affected by non-indigenous plants, through the addition of organic detritus derived from vascular plants in the diets together with a decreased contribution of diatoms, although the impacts may differ among different functional feeding groups of macrobenthos. Highlights: The food sources of intertidal macrobenthos were affected by non-indigenous plants. Detritus derived from vascular plants is assimilated into the tissues of macrobenthos. The impacts may differ among different functional feeding groups of macrobenthos.